Investigating the Use of Mobile-Assisted Language Learning (MALL) for Listening Instructions in SMAN 5 Tanjungpinang - Zidan Dwi Khalfani Kareem; Sihombing, Vebiyola; Santo Andika Jaya; Sarah Stefani Simbolon; Dhipo Dzaki Aryuda; Erwin Pohan (The Study Program of English Education of Palangka Raya University, 2025)
Listening is essential for effective communication but often poses challenges in traditional teaching settings, where exposure to authentic materials is limited (Vandergrift & Goh, 2012). However, Mobile-Assisted Language Learning (MALL) provides mobile access to interactive audio content, enabling adaptive learning experiences (Burston, 2014) and continuous exposure to varied accents (Godwin-Jones, 2017). This study explores the implementation of MALL for listening instructions in SMAN 5 Tanjungpinang, focusing on the research questions: “Has SMAN 5 Tanjungpinang incorporated MALL into their teaching practices?” and “How does MALL contribute to improving SMAN 5 Tanjungpinang students' listening skills?” This qualitative research employs observation and semi-structured interviews to examine MALL's application in real classroom settings, aligning with the (Creswell, 2014) emphasis on context and utilizing thematic analysis to identify emerging patterns (Braun & Clarke, 2013). Findings reveal that while SMAN 5 Tanjungpinang has started incorporating MALL, there is significant potential to enhance its integration further and positively impact students' listening skills. These results highlight the importance of integrating mobile technology into educational curricula to enhance language learning outcomes.